1999
DOI: 10.1074/jbc.274.50.35415
|View full text |Cite
|
Sign up to set email alerts
|

Further Biochemical and Kinetic Characterization of Human Eukaryotic Initiation Factor 4H

Abstract: A cDNA encoding human eukaryotic initiation factor (eIF) 4H was subcloned into a bacterial expression plasmid for purification of recombinant protein. Recombinant human eIF4H (heIF4H) was purified to greater than 95% homogeneity and shown to have similar physical characteristics to eIF4H purified from rabbit reticulocyte lysate as described previously. Functional studies have revealed that recombinant heIF4H functions identically to rabbit eIF4H in stimulating protein synthesis, and the ATP hydrolysis and heli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 43 publications
6
71
0
Order By: Relevance
“…This suggests that in vivo, 4B and 4H compete with one another for interaction with and regulation of 4AI. Although 4B and 4H appear to be ubiquitously expressed (Nomura et al 1994;Richter et al 1999), tissue-specific variations in their mRNA levels suggest that individual tissues contain unique ratios of the two proteins. For example, 4H transcript levels are twice those of 4B in the brain, whereas 4B transcripts are circa four times those of 4H in skeletal muscle ).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that in vivo, 4B and 4H compete with one another for interaction with and regulation of 4AI. Although 4B and 4H appear to be ubiquitously expressed (Nomura et al 1994;Richter et al 1999), tissue-specific variations in their mRNA levels suggest that individual tissues contain unique ratios of the two proteins. For example, 4H transcript levels are twice those of 4B in the brain, whereas 4B transcripts are circa four times those of 4H in skeletal muscle ).…”
Section: Discussionmentioning
confidence: 99%
“…(iii) Pateamine may uncouple the coordinated activities between eIF4A f and eIF4B and͞or eIF4H. eIF4B, and eIF4H stimulate the ATPase (3, 5, 6, 34), RNA-binding (5,34,35), and helicase activities (4, 6, 10, 36) of eIF4A f and eIF4A c . This model would suggest that tight regulation of eIF4A f activity is essential for optimal translation initiation on cap-dependent mRNA templates, as well as on eIF4A-dependent IRESes (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…This gene is ubiquitously expressed and it is suggested that it is involved in translation initiation and in stabilizing attributes during RNA binding, ATP hydrolysis and RNA duplex unwinding [175].…”
Section: The Single Copy Gene Part Of the Wbs Regionmentioning
confidence: 99%